Characterization of Dolomite Reservoir Pore‐Throat Structure Based on Cast Thin Section Image Analysis and Fractal Theory: A Case Study of Middle Jurassic Dolomite in the Southern Depression of Qiangtang Basin, Northern Tibetan Plateau, China - Zhonglin Wang; Jiashan Lin; Shengfu Wen; Youli Wan; Yuan Xie (Energy Science & Engineering)
ABSTRACT The Middle Jurassic Buqu Formation dolomite in the Qiangtang Basin, northern Tibetan Plateau, is characterized by strong heterogeneity, low porosity, and low permeability, making the evaluation of its pore structure a challenging task. In this study, dolomite samples were extracted from boreholes and examined using cast thin sections and scanning electron microscopy. Combined with petrophysical analysis, we investigated the distribution and fractal characteristics of the pores, and explored the relationship between the fractal dimension and reservoir petrophysical parameters, pore structure parameters, and pore genesis. The results indicate that: (1) The types of storage spaces in the Buqu Formation dolomite in the study area include selective intercrystalline pores, nonselective intercrystalline pores, and fractures, with a relatively concentrated pore size distribution. (2) The R² of the fractal fitting curve of the large pore equivalent mercury injection is greater than 0.95, indicating that the large pores of the dolomite reservoir exhibit fractal characteristics, which can be used to characterize the pore structure. The pores are complex and diverse, with strong interlayer (overall) heterogeneity. (3) The fractal dimension of large pores has a good correlation with petrophysical parameters and pore structure parameters, and can be used for the quantitative characterization of the pore structure of the Buqu Formation dolomite reservoir. (4) The pores of carbonate sediments formed by sedimentation are the basis of the storage space and pore‐throat structure of this set of reservoirs, and the subsequent dolomitization and dissolution processes jointly control the heterogeneity of the pore‐throat structure.